Microbiological features of pathogens from sputum in patients with purulent-destructive complications community-acquired pneumonia - Bakumenko, A (Annals of Mechnikov's Institute, 2020)
The paper analyzes data microbiological examination of sputum that has been deleted in patients with suppurative destructive complications CAP. The species composition of the microflora and the number of different genera of microorganisms in patients with lung abscess and empyema empiyemu. Studied the composition of microbial associations. It was established that most of monoculture sown S. pyogenes and C. albicans. C. albicans was removed in two-component associations of S. epidermidis, S. pneumoniae, S. pyogenes and in rare cases with P.aeruginosa.